2019
DOI: 10.1097/htr.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Concussion Management: A Model for Outpatient Concussion Management in the Acute and Post-Acute Settings

Abstract: Objective: To describe a model of multidisciplinary concussion management and explore management methods in the acute and post-acute settings. Setting: A multidisciplinary concussion management program within a large health system. Participants: Patients with sports and non–sports-related concussions aged 14 to 18 years with persisting concussion symptoms at 4 weeks postinjury or beyond. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 55 publications
0
33
0
15
Order By: Relevance
“…We identified six studies (three prospective, [38][39][40] three retrospective [41][42][43] ) that evaluated PT and timing of increased activity on PTH in youth. Some reported headache improvement, whereas others found modest or no effect.…”
Section: Physical Therapy and Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…We identified six studies (three prospective, [38][39][40] three retrospective [41][42][43] ) that evaluated PT and timing of increased activity on PTH in youth. Some reported headache improvement, whereas others found modest or no effect.…”
Section: Physical Therapy and Exercisementioning
confidence: 99%
“…There was a significant effect in the intervention group when total postconcussion symptoms scores were evaluated, but significance testing comparing headache outcomes in the two groups was NR. 39 A prospective study found that completing diagnostic exertional testing did not significantly reduce headache symptom scores 24 h after testing. This study was limited by a high drop-out rate (31%).…”
Section: Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Such an interdisciplinary approach allows for the whole to be more than the sum of its parts and for intervention to be harmonized across disciplines to the benefit of the client. Although "speech therapy" is identified in some instances as a specialty to be involved with people who have cognitive complaints after concussion (Bazarian, 2019;Hardin & Kelly, 2019), a description of CCDs and involvement of SLPs is not offered in many publications describing either multidisciplinary or interdisciplinary models (e.g., Bailey et al, 2019;Scratch et al, 2019). Furthermore, even though many SLPs are aware of CCDs, most assessments used by interdisciplinary partners in TBI care, including concussion, do not include tools or items that would highlight CCDs that would then easily lead to referral for SLP services.…”
Section: Training: the Medical Slp And The School-based Slpmentioning
confidence: 99%
“…Ce système de gestion des symptômes et de choix d'activités a été couplé au concept clé « maximiser ce qui fait du bien et minimiser ce qui fait du mal » (Beni, 2019). La marche extérieure a été imposée à FB, comme activité quotidienne, car les bienfaits d'une activité à faible intensité sur le processus de récupération sont aujourd'hui largement reconnus (Bailey et al, 2019). La marche est donc imposée à tout sportif qui consulte à la suite d'une CC.…”
Section: La Gestion Des Symptômes Post-commotionnelsunclassified